The impacts of interaction of audit litigation and ownership structure on audit quality - Riyadh Jassim Al Abdullah; Mawih Kareem Al-Ani (Future Business Journal, 2021)
This study examines the impact of the interactions of audit litigation and ownership structure on audit quality by Big 4 and non-Big 4 audit firms in Oman. This study uses modified audit opinion~as proxies for audit quality, binary variable for audit litigation and percentage of shares owned by large shareholders and minority shareholders (consisting of Arab [non-GCC] shareholders) for ownership structure. The study uses size, risk, types of activity and ages of the firms as control variables. For the analysis and explanation of results descriptive statistics, correlation, regression techniques and T-test are used. Based on a sample of 107 listed companies on Muscat Securities Market (MSM) for 2013-2017, we find that audit litigation has a significant impact on audit quality for Big 4 audit firms, but not for non-Big 4 audit firms. Also, the results indicate that there is no difference between Big 4 and non-Big 4 audit firms as far as litigation risk is concerned.
Keywords: G32; M40; M42; 650; Audit litigation; Audit quality; Emerging economy; Oman; Ownership structure